Pengembangan Buku Penuntun Praktikum Energi dalam Sistem Kehidupan dengan Model Argument Driven Inquiry (ADI) - Tirta Sari; Neni Hasnunidah; Rini Rita T. Marpaung (Universitas Lampung, 2018)
This study aims to describe the validity and practicality of guidebook of energy in living systems developed with ADI model. This research design used was R D with 4-D model covering th stages of define, design, develop, and disseminate. However, the disseminate stages were not carried out. Data analysis used qualitative descriptive. The developed product was made with an attractive cover and uses cambria font letters 14 and 12. Each practicum consists of labels, theory, goals, questions, tools, materials, work steps, arguments on a whiteboard include (claim, data/evidence, warrant, and backing), argumentation sessions and reports. Experimental and practitioner validation test results showed that the average ideality scores are categorized as